Specific Antibody Production by Blood B Cells is Retained in Late Stage Drug-naïve HIV-infected Africans - Lydie Béniguel; Evelyne Bégaud; Fabrice Cognasse; Philippe Gabrié; Christophe D. Mbolidi; Mary A. Marovich; Céline Cazorla; Frédéric Lucht; Christian Genin; Olivier Garraud (Clinical and Developmental Immunology)
Unseparated peripheral blood mononuclear cells (PBMCs) obtained from drug-naïve African individuals living in a context of multi-infections and presenting with high viral load (VL), were cultured in vitro and tested for their ability to produce antibodies (Abs) reacting with HIV-1 antigens. Within these PBMCs, circulating B cells were differentiated in vitro and produced IgG Abs against not only ENV, but also GAG and POL proteins. Under similar experimental conditions, HAART treated patients produced Abs to ENV proteins only. The in vitro antibody production by drug-naïve individuals' PBMCs depended on exogenous cytokines (IL-2 and IL-10) but neither on the re-stimulation of reactive cells in cultures by purified HIV-1-gp 160 antigen nor on the re-engagement of CD40 surface molecules. Further, it was not abrogated by the addition of various monoclonal Abs (mAbs) to co-stimulatory molecules. This suggests that the in vitro antibody production by drug-naïve individuals' PBMCs resulted from the maturation of already envelope and core antigen-primed, differentiated B cells, presumably pre-plasma cells, which are not known to circulate at homeostasy. As in vitro produced Abs retained the capacity of binding antigen and forming complexes, this study provides pre-clinical support for functional humoral responses despite major HIV- and other tropical pathogen-induced B cell perturbations.